Differential expression of nitric oxide synthases in porcine aortic endothelial cells during LPS-induced apoptosis - Bernardini Chiara; Greco Francesca; Zannoni Augusta; Bacci Maria Laura; Seren Eraldo; Forni Monica (BMC, 2012)
Abstract Background It is well known that nitric oxide (NO) is generated by a family of constitutively (nNOS and eNOS) or inducibly (iNOS) expressed enzymes and takes part in different aspects of the inflammatory response; nevertheless, its effective role in the pathogenesis of multiple organ dysfunction and septic shock is not fully understood. Methods To investigate the Nitric Oxide Synthases (NOSs) expression in endothelial cells during endotoxin exposure and the involvement of NO in lipopolysaccharide (LPS)-induced apoptosis, primary cultures of porcine Aortic Endothelial Cells (pAECs) were exposed to LPS for different time periods (1-24 h) and to LPS + L-NAME (15 h). Results Lipopolysaccharide induced an increase in mRNA and protein iNOS expression; on the contrary, the expression of eNOS was decreased. Furthermore, NOSs localisation was in part modified by LPS treatment. No alteration in the total level of Nitric Oxide was observed. L-NAME (5 mM) addition determined a slight decrease of LPS-induced apoptosis. Conclusions Endotoxin treatment strongly influenced NOS expression with an upregulation of iNOS and a simultaneous down regulation of eNOS. Moreover, in our model, the involvement of NO on LPS-induced apoptosis is very modest, suggesting that different pathways are involved in the regulation of this process.